Kajian Literatur Tentang Strategi Pembelajaran Multikultural pada Pendidikan Anak Usia Dini - Azizah Hanum OK; Rekha Dyta Amelia; Siti Fadhilah Harahap (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Multicultural education in early childhood is essential for fostering tolerance, empathy, and respect for diversity. As a multicultural nation, Indonesia’s cultural, linguistic, and religious diversity needs to be systematically introduced through early education. This study aims to analyze multicultural learning strategies in Early Childhood Education (ECE), including storytelling, role-playing, songs, games, and experiential culturally based learning. This study employs a library research approach by reviewing relevant scholarly sources. Data were analyzed using qualitative descriptive methods through classification, interpretation, and thematic synthesis. The findings reveal that multicultural learning strategies are most effective when implemented through play-based and collaborative approaches aligned with children's developmental characteristics. The integration of cultural elements into learning enables children to understand diversity concretely while developing social competence, communication skills, cooperation, and appreciation for different cultural backgrounds. Furthermore, teachers play a crucial role in designing inclusive learning environments that encourage meaningful interactions among children from diverse backgrounds. These findings highlight the role of multicultural education in early childhood as a foundation for nurturing inclusive individuals capable of living harmoniously in diverse societies while strengthening national unity and promoting social cohesion from an early age.